Analysis The Effect of Implementing Green Marketing Strategy on Consumers Purchase Decision at The Body Shop Palembang - Ayu Wandira Randika; Hera Febria Mavilinda (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2023)
This study aims to determine the effect of implementing green marketing strategies on purchasing decisions at The Body Shop Palembang. The variables used are green product, green price, green place, green promotion, and purchasing decisions. The population in this study are consumers of The Body Shop in Palembang. The sample in this study was 100 respondents who were determined by purposive sampling technique. This study used quantitative methods and data collection using primary data in the form of questionnaires. The data analysis technique used is instrument test, classical assumption test, multiple linear regression analysis, and the coefficient of determination. The results showed that green marketing strategy has a positive and significant effect simultaneously or partially on purchasing decisions at The Body Shop Palembang City with a significant influence of 58.8%. The results of the regression equation show that the dominant variable in this study is the green product with a coefficient of 0.430.Keywords: Green Marketing, Purchase Decision.